Active ingredients and mechanisms of peony seed blended oil in diabetes treatment using Kunming mice: Insights from GC–MS, network pharmacology, and experimental verification - Yuning Gu; Fengliang Zhong; Tiantian Sun; Zirui Chang (Journal of Functional Foods)
Soybean oil, rich in linoleic acid, plays a crucial role in lowering blood lipids and cholesterol, which helps prevent cardiovascular diseases. The lecithin content in soybeans is also essential for the development and growth of the nervous system, blood vessels, and brain. Canola oil, with a higher level of Omega-3 polyunsaturated fatty acids, helps soften blood vessels and can prevent atherosclerosis, offering benefits for both cardiovascular and cerebrovascular health. Blending these oils can create a synergistic effect, maximizing their health benefits. Furthermore, all three oils should meet the national standard GB 2716–2018 for vegetable oils. Peony seed oil, high in unsaturated fatty acids, particularly α-linolenic acid, has shown significant hypoglycemic effects. To enhance these effects, soybean and canola oils, which contain beneficial components like linoleic acid and oleic acid, were blended with peony seed oil. This study aimed to evaluate the combined hypoglycemic potential of these oils through in vitro and in vivo experiments, supported by network pharmacology and molecular docking analyses to explore the underlying mechanisms. The research provides valuable insights into the potential therapeutic use of this blended oil in diabetes management, offering a natural alternative for hypoglycemic treatments. Zhao et al. (2021), Suyun et al. (2024) (Suyun et al., 2024; Zhao et al., 2021). In vitro and in vivo experiments, as well as network pharmacology and molecular docking analysis, were conducted to evaluate the hypoglycemic effects of peony seed oil, soybean oil, rapeseed oil, and their blends. GC–MS analysis identified nine major components, including γ-sitosterol, α-linolenic acid, and linoleic acid (Journal of Food Biochemistry, 2020). The results showed that the optimal blend ratio of peony seed oil to soybean and rapeseed oils was 60:27:11, which significantly inhibited α-amylase and α-glucosidase activities. Network pharmacology and molecular docking revealed that α-linolenic acid and linoleic acid are key active compounds, targeting PPARG and MAPK3, primarily through the PPAR and IL17 signaling pathways. This multi-component, multi-target, and multi-pathway approach offers potential synergistic benefits for diabetes treatment. The study provides valuable insights for the development of novel hypoglycemic agents (Yang, 2014 (Yang, 2014)).The study evaluated the combined hypoglycemic effects of peony seed oil, soybean oil, rapeseed oil, and their blends through in vitro and in vivo experiments, supported by network pharmacology and molecular docking analyses. GC–MS analysis identified nine major components, including γ-sitosterol, α-linolenic acid, and linoleic acid (Zhao et al., 2021; Suyun et al., 2024 (Suyun et al., 2024; Zhao et al., 2021)). The optimal blend ratio of peony seed oil to soybean and rapeseed oils was found to be 60:27:11, which significantly inhibited α-amylase and α-glucosidase activities. Network pharmacology and molecular docking indicated that α-linolenic acid and linoleic acid are key active compounds, targeting PPARG and MAPK3, primarily through the PPAR and IL17 signaling pathways (Journal of Food Biochemistry, 2020). This multi-component, multi-target, and multi-pathway approach offers synergistic benefits for diabetes treatment. The research underscores the potential of this blended oil as a natural alternative in managing diabetes, providing valuable insights for its therapeutic application (Yang, 2014 (Yang, 2014)).